1 The Public Records of the Colony of Connecticut 196 (J. Hammond Trumbull ed., 1850) (enacted 1646) - (:unkn) unknown (My University, 1646)
"It is ordered, that no man within this iurisdiction shall, directly or indirectly, amend, repair, or cause to bee amended or repaired, any gun, small or greate, belonging to any Indian, nor shall endevour the same, nor shall sell or give to any Indian, directly or indirectly, any such gun, or any gunpowder, or shott, or leade, or shot moulde, or any millitary weopons, or armour, vpon paine of ten pound fine for ev'y offence at least,& that the Court of Assistants shall have power to increase the fine or to impose corporall punishment wheare a fine cannot bee had, at their discretion."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES